Enhancing pseudocapacitive energy storage system performance with electrodeposited CuSx and CoSx biphasic transitional metal sulfide (TMS) based nanostructured electrode on nickel foam - Mottakin M.; Selvanathan V.; Su'ait M.S.; Razali S.A.; Islam M.A.; Ibrahim M.A.; Muhammad G.; Akhtaruzzaman M. (Elsevier Ltd, 2025)
This study investigated the pseudocapacitive energy storage system of biphasic CuSx and CoSx electrodeposited on nickel foam (NF). XRD, FESEM, and EDX show the formation of nano-flower-shaped biphasic layer on NF. The biphasic electrode shows higher areal specific capacitance (Csp) than the single-layered NF/CuSx and NF/CoSx electrodes. The Csp of the NF/CuSx/CoSx drops by 42 % as the scan rate (?) rises from 5 mV s?1 to 20 mV s?1. Electrode polarization and reduced ion migration occurring with rapid scan rates are responsible for this decrement. Galvanostatic charge-discharge (GCD) analysis showed that Csp declined from 11.42 to 9.63 F cm?2, and the retained Csp was 84 % as the current density shifted from 4 to 8 mA cm?2. The energy density of 0.30 mWh.cm?2 and power density of 1.57 mW cm?2 imply significant energy storage capability of the electrode. The kinetic analysis indicates that 78 % of the capacitance is diffusion-controlled process in the NF/CuSx/CoSx electrode. The b-value of around 0.7 suggests that the pseudocapacitance mostly originates from diffusion-controlled processes. The poor cyclic stability of NF/CuSx/CoSx was demonstrated by only upholding 61 % of its original Csp after 500 cycles. However, the higher coulombic efficiency indicates that a greater proportion of the electrical charge is stored in the supercapacitor. The study explores the biphasic design of copper and cobalt sulphide-based electrodes as potential pseudocapacitive energy storage system applications such as supercapacitors and supercapatteries. ? 2023 Elsevier Ltd